Efficacy of Combined Therapy of ACTH plus Vigabatrin Compared to ACTH Alone for Treatment of Infantile Spasm-A RCT - Sumi, Samsun Nahar; Mistry, Banita; Habib, Md Ahsan; Chandra, Mahua; Hoque, Seikh Azimul; Saha, Narayan Chandra (Bangladesh Journal of Child Health, 2023)
Background: Infantile spasms (epileptic spasm) is difficult to treat and has a high morbidity. So it’s crucial to initiate an early effective therapy. ACTH, Prednisolone and Vigabatrin have shown better efficacy on cessation of spasms. Objective: To compare the efficacy and tolerability of combined ACTH and Vigabatrin with ACTH alone in treatment of infantile spasms. Materials & Methods: This randomized controlled trial was conducted from June, 2017 to June, 2018 at outdoor and indoor, department of Paediatric Neurology of National Institute of Neurosciences and Hospital, Dhaka. Fifty (50) patients aged 2 months to 24 months who had a clinical diagnosis of infantile spasms and hypsarrhythmia (classical or modified hypsarrhythmia) in EEG were enrolled. With parent’s written informed consent, they were randomized (1:1 by lottery method) into two groups, 25 in each. One group got ACTH only and another group got both ACTH and vigabatrin. At the end of the treatment two groups were compared regarding efficacy and safety of the drugs. Result: The primary outcome was assessed in 50 children at 91st day. The primary outcome was cessation of spasms from 14th day to 42nd day after initiation of therapy. Cessation of spasms (between 14 to 42 days) occurred in 18 children (72%) in combination therapy and 11 children (44%) in hormonal therapy (p=0.045). Treatment response was faster on combination therapy (p=0.001). Treatment was well tolerated in both groups with few adverse effects. Conclusion: Combination therapy of ACTH plus Vigabatrin was found better than ACTH therapy alone in cessation of infantile spasms. BANGLADESH J CHILD HEALTH 2022; VOL 46 (1) : 14-18